Shoulder Bag Design from Used Denim Material with Hand Embroidery Technique Application - Sheva, Early Fathia (Institut Seni Indonesia Yogyakarta, 2024)
Piles of denim waste are a problem for the environment, so it is necessary to find the right solution. One of them is by reprocessing used jeans made from denim into new products that have use value and selling value with the concept of upcycling, in the form of shoulder bags.The process of designing this work follows the reference of S.P. Gustami's creation method, which in making this work goes through three stages, namely exploration to explore ideas through various references, the design process that considers several aspects, and the stage of realizing ideas into finished products. The target to be obtained is a shoulder bag product that is decorated using hand embroidery technique.The product produced from this design project is a shoulder bag with denim main material from used jeans that takes the visualization of the Moon Goddess story. The technique used in this design uses the application of hand embroidery techniques as an addition to add aesthetic value to the product. The details of this addition will bring out the texture produced from the hand embroidery technique.ABSTRAKTumpukan limbah denim menjadi masalah tersendiri bagi lingkungan,sehingga perlu dicarikan solusi yang tepat. Salah satunya dengan mengolahkembali celana jeans bekas berbahan denim menjadi produk baru yangmemiliki nilai guna dan nilai jual dengan konsep upcycle, berbentuk tas bahu.Proses perancangan karya ini mengikuti acuan metode penciptaan S.P.Gustami, yakni dalam membuat karya ini melalui tiga tahap, berupa eksplorasi untuk menggali ide melalui berbagai referensi, proses perancangan yang mempertimbangkan beberapa aspek, dan tahap perwujudan ide menjadi produk jadi. Target yang ingin diperoleh adalah produk tas bahu yang diberi hiasan dengan menggunakan teknik hand embroidery. Produk yang dihasilkan dari proyek perancangan ini berupa tas bahu dengan material utama denim dari celana jeans bekas yang mengambil visualisasi cerita Dewi Bulan atau Moon Goddess. Teknik yang digunakan dalam perancangan ini menggunakan aplikasi teknik hand embroidery sebagai imbuhan untuk menambah nilai estetis pada produk. Detail imbuhan ini akan memunculkan tekstur yang dihasilkan dari teknik hand embroidery.